Executive Committee Minutes 2012-02-16 - Academic Senate:::::::::
Revision to the Philosophy Curriculum approved for consent calendar. Revision to the Anthropology Major approved for consent calendar. Revision to the Sociology Major approved for consent calendar. Revision to the Excellence in Teaching Award policy approved for Senate agenda. Sustainability Structure Recommendation discussed.